Evangeline vs. the machine [compact disc] - Church, Eric (Singer) (EMI Nashville, 2025)
Eric Church's eighth studio album features eight new songs, including "Darkest Hour" and 'Hands of Time." A seven-time ACM Award-winner, four-time CMA Award-winner (including the highest honor for Entertainer of the Year) and ten-time Grammy-nominee, Church has amassed a passionate fan base around the globe known as the Church Choir, plus a critically acclaimed catalog of music. This followed his Gold-certified Desperate Man, which earned a Grammy nomination for Best Country Album (his third nod in the category) and prior releases, including the platinum-certified Sinners Like Me ("How Bout You," 'Guys Like Me"), Carolina ('Smoke a Little Smoke," "Love Your Love the Most ) and Mr. Misunderstood ('Record Year," 'Round Here Buzz"), the two time platinum-certified The Outsiders ("Like a Wrecking Ball," 'Talladega") and the three time platinum-certified Chief ("Springsteen," 'Drink In My Hand"), as well as 36 gold, platinum and multiplatinum songs.